2019
DOI: 10.5254/rct.19.80452
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Spherical Approximation: Elongated Free Volume Holes in Rubbers: A Positron Annihilation Study

Abstract: The free volume fraction, a key parameter for the understanding of mechanical and transport properties of polymers, has been evaluated in a fluoroelastomer and a cis-polyisoprene rubber by means of positron annihilation lifetime spectroscopy and dilatometry. The evaluation showed that the assumption of elongated holes allows one to get a very good agreement between the free volume fraction experimentally determined and the theoretical expectation based on the lattice-hole model. On the other hand, systematic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
3
3
0
Order By: Relevance
“…Similar findings were found in various elastomers [ 124 , 132 , 133 ]: in these cases, too, holes are well represented by flattened cylinders. Therefore, it seems that flattened holes are more common than spherical holes, in our investigated polymers.…”
Section: Discussion Of Some Pals Results In Polymeric Systemssupporting
confidence: 86%
See 2 more Smart Citations
“…Similar findings were found in various elastomers [ 124 , 132 , 133 ]: in these cases, too, holes are well represented by flattened cylinders. Therefore, it seems that flattened holes are more common than spherical holes, in our investigated polymers.…”
Section: Discussion Of Some Pals Results In Polymeric Systemssupporting
confidence: 86%
“…In particular, in polybutadiene-polyisoprene blends we found that p decreases almost linearly with the content of polyisoprene volume fraction (Figure 13), while the presence of acrylonitrile in acrylonitrile-butadiene blends does not change, within the errors, the value of p found for pure butadiene. Similar findings were found in various elastomers [124,132,133]: in these cases, too, holes are well represented by flattened cylinders. Therefore, it seems that flattened holes are more common than spherical holes, in our investigated polymers.…”
Section: Coupling Pals and Dilatometry: An Alternative Route To The F...supporting
confidence: 85%
See 1 more Smart Citation
“…Similar results were also obtained for a fluoroelastomer and for a cis-polyisoprene rubber. 20 It is remarkable that a typical size of holes at the glass transition for different elastomers matches quite well to l, a parameter related to reptation motions and largely independent of the macromolecular structure.…”
Section: Discussionmentioning
confidence: 89%
“…The results well fitted the theoretical free volume fractions, but at the price of introducing a fictitious occupied volume, that is, not corresponding to the one provided by the theory. In a previous paper concerning cis-polyisoprene, 20 we used an occupied volume in agreement with the theory and showed that it is possible to solve this contrast by assuming cylindrical holes forming the free volume in cis-polyisoprene. This stimulated us to investigate the shape of the free volume holes in other rubbers and we turned to blends containing isoprene.…”
Section: Introductionmentioning
confidence: 99%